The relationship between physical activity and depression in college students: the parallel mediating role of mindfulness and life satisfaction - Wang, Anning; Shi, Longjuan; Wang, Tong (Frontiers in Public Health, 2025)
ObjectiveTo explore the relationship that mindfulness and life satisfaction have in the process of alleviating depression through physical activity in Chinese universities and the mediating role of life satisfaction and mindfulness in this process.MethodsParticipants were 508 college students (240 males, 268 females, mean age 19.90, SD = ±1.10). Psychosocial tests, including the Physical Activity Rating Scale (PARS-3), the Positive Attention Awareness Scale (MAAS), the College Student Life Satisfaction Scale (CSLSS), and the Patient Health Questionnaire-9 (PHQ-9), were completed. Correlations of variables were calculated using Pearson’s test. The mediation model was tested using the SPSS 26.0 PROCESS macro plug-in and regression bootstrap.ResultsPhysical activity showed a negative correlation with depression (β = −0.0045, p < 0.001), mindfulness and life satisfaction showed a correlation between physical activity and depression, and more importantly, physical activity was negatively correlated with depression through the parallel mediating effect of mindfulness and life satisfaction, with a total mediating effect of 53.54%.ConclusionBy increasing college students’ participation in physical activity, it helps to promote their mindfulness and life satisfaction, which is the key to reducing depression and promoting college students’ mental health.